Applicability of Evoked Auditory Brainstem Responses with Complex Stimuli in Adults with Hearing Loss - Peixe, Bruna Pias; Silva, Débora Durigon da; Biaggio, Eliara Pinto Vieira; Bruno, Rúbia Soares; Sanguebuche, Taissane Rodrigues; Garcia, Michele Vargas (International Archives of Otorhinolaryngology, 2018)
Introduction The use of the speech-evoked auditory brainstem response (ABR) shows how the brainstem operates up to the subcortex in a more complex manner than when the click-evoked ABR is used.Objective To study the applicability of the speech-evoked ABR in adults with hearing loss.Methods The sample was composed of a study group of 11 subjects, with ages ranging between 18 and 59 years, and auditory thresholds within normal standards, with loss of up to 65 dB at high frequencies or up to moderately severe symmetric sensorineural hearing loss. The sample underwent a basic audiological assessment, as well as speech-evoked ABR and click-evoked ABR, in which waves I, III and V, and V, A, C, D, E, F were respectively marked. The electrophysiological assessments were performed using the SmartEP device (Intelligent Hearing Systems, Miami, FL, US).Results For the speech-evoked ABR, the reference values were used in the identification and analysis of the study group. Those values found for the study group were: V = 8.56; A = 10.97; C = 21.33; D = 29.51; E = 37.93; F = 46.96; and O = 55.97. In the comparison between groups, the study group presented an increase in latency only in wave C.Conclusion The speech-evoked ABR can be performed in subjects with up to moderately severe hearing loss, and the test proved to be appropriate, because, unlike the click-evoked ABR, the former does not suffer influence of peripheral hearing loss.
Keywords: hearing; electrophysiology; auditory evoked response; hearing loss